STEM CELL HIERARCHY AND IMMUNE TOLERANCE IN BONE MARROW MICHES: MECHANISMS AND EMERGING PERSPECTIVES - Elyusaputra, Harry; Anggriawati, Moudy (Journal of Stem Cell Research and Tissue Engineering, 2025)
Bone marrow niches play a crucial role in regulating the hierarchy of hematopoietic stem cells (HSCs) and immune tolerance. In this microenvironment, interactions between niche cells and molecular components such as Nitric Oxide (NO) and the CD200 protein influence HSC function. NO acts as a signaling molecule that supports HSC proliferation at low concentrations and promotes differentiation at higher concentrations. HSCs with high NO production are often located near CD200-rich capillaries, providing protection from immune responses. Additionally, the signaling pathway involving IFT20, CD200, eNOS, and autophagy supports cellular homeostasis and the survival of cells under stress, including in cancer. The expression of CD200 in capillaries contributes to a tolerogenic immune environment, protecting tissues from excessive inflammation. However, excessive CD200 expression can be exploited by tumor cells to evade immune detection. This review highlights the critical role of the bone marrow microenvironment in regulating stem cell behavior and immune tolerance, offering insights into how these molecular interactions govern stem cell fate and tissue homeostasis. A deeper understanding of these pathways can pave the way for novel therapeutic strategies in blood disorders, cancer, and inflammatory diseases. By unraveling the intricate molecular interactions within the bone marrow niche, this research provides new perspectives on stem cell regulation and immune tolerance, with implications for improving clinical outcomes in stem cell-based therapies.